Research on enhancing marine microalgae biomass Tetraselmis sp. for nitrogen and phosphorus removal from brakish-salt water rich in nutrients - Đặng Thị, Thanh Lộc; Van Tuan, Le; Nguyen Thi, Thu Lien; Nguyễn Công, Phúc Lộc; Truong Quy, Tung; Ta Ngoc, Tri; Duong Thanh, Chung; Phan Hai, Phong (Hue University Journal of Science: Natural Science, 2024)
This study investigates the cultivation of Tetraselmis sp., a marine microalgae species, in seawater enriched with elevated levels of nutrient salts (N, P). The primary objective was to determine the suitable growth conditions for Tetraselmis sp., considering variations in nutrient composition, pH levels, initial inoculum density, and differing initial TN:TP ratios. Results indicate robust growth of Tetraselmis sp. in F/2 seawater medium with a salinity of 30 ‰ and pH 8, with initial inoculum densities ranging from 5% to 10%. Tetraselmis sp. exhibited strong growth potential in environments with elevated nutrient salt concentrations (N, P). Specifically, as TN concentration increased from 9.7 to 56.3 mg/L and TP concentration rose from 0. 1 to 3.7 mg/L, cell density increased from 6.98×105 (cells/mL) to 1.34×106 (cells/mL) after a 15-day cultivation period. Total phosphorus treatment efficiency ranged from 82% to 100%. Total nitrogen treatment efficiency ranged from 97% to 83% for initial T-N concentrations of 10 to 25 mg/L. However, with higher T-N concentrations ( 56 mg/L), the treatment efficiency reached only 58% after 15 days of cultivation. These findings highlight the significant potential of cultivating Tetraselmis sp. for N and P removal from brackish-salt water rich in nutrients in Vietnam.